PENGARUH PENERAPAN GAYA KEPEMIMPINAN OTENTIK, MOTIVASI KERJA, DISIPLIN KERJA, DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN - Rahman Muhammad Ihsan (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
Abstract: The purpose of this study is to be able to test and determine the factors that can affect Employee Performance, which include Authentic Leadership, Motivation, Discipline, and Career Development at PT. Polychemie asia pacific is great for improving employee performance. The data analysis method used is the Statistical Package for the Social Sciences (SPSS), Structural Equation Modeling (SEM) listrel by distributing questionnaires to 384 employees with supervisory level and below who work at PT. Polychemie asia pacific is beautiful as the research sample. The results show that Authentic Leadership with a value of 0.19, Motivation with a value of 0.47 Career Development with a value of 0.04 significantly affect employee performance. Meanwhile, the Discipline variable has no significant effect on Employee performance. In accordance with the results of the study, the researcher gives advice to the company to be able to improve the company's employee performance, as well as ensure and comply with the requirements in accordance with applicable laws, regulations and procedures and apply steps to achieve company goals.Keyword: Authentic Leadership, Motivation, Discipline, Career Development, Employee Performance, Industrial